Preliminary studies for the attract-and-kill strategy against Culex pipiens - Kioulos, E.; Koliopoulos, G.; Couladouros, E. A.; Michaelakis, A. (ENTOMOLOGIA HELLENICA, 2008)
The attract-and-kill strategy requires an intelligent and an efficient combination of an attractant and a killing agent such as a pheromone and an insecticide respectively. The production of the synthetic oviposition pheromone of the mosquito species Culex quinquefasciatus (Diptera: Culicidae) was already achieved and its combination with three different insecticides were tested. Furthermore three larvicides, an insect growth regulator (pyriproxyfen), an organophosphate (temephos) and a microbial (Bacillus thuringiensis subsp. israelensis) were tested in the laboratory against Culex pipiens biotype molestus (Diptera: Culicidae) as agents that can keep water free from mosquito larvae. Larvicidal activity, over a 50-day period, revealed good results primary for temephos and secondary for pyriproxyfen. Temephos killed all the hatched larvae (100%) while pyriproxyfen was effective the first five days (>90%) and for the following days mortality was in a rate between 60 and 80%. The results from oviposition bioassays revealed that except temephos all the tested larvicidals repel gravid females of laying eggs for the first two days. However, when synthetic pheromone is combined with the three larvicidals, temephos and microbial agent followed the same attractant pattern as synthetic pheromone independently.